Case Report: Prolonged Neutropenia in Premature Monoamniotic Twins With SARS-CoV-2 Infection Acquired by Vertical Transmission - Scholz, Anna S.; Wallwiener, Stephanie; Pöschl, Johannes; Kuss, Navina (Frontiers in Pediatrics, 2022)
Background: Vertical transmission of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection is a highly debated topic in the current pandemic situation. Early neonatal SARS-CoV-2 infection is rare and generally mild. Long-term data describing symptoms after COVID-19 in premature neonates is scarce. Case presentation: Two premature, monoamniotic neonates were born by cesarean section to a mother 5 days after onset of symptomatic COVID-19. On day three of life both neonates developed hyperthermia, respiratory distress, and hematological changes, of which neutropenia persisted for over 40 days. Nasopharyngeal swabs for SARS-CoV-2 turned positive four days after delivery although the neonates were strictly isolated. Both neonates showed nearly identical time courses of ct values. Conclusion: Our case report revealed prolonged low absolute neutrophil counts in two preterm neonates with symptomatic SARS-CoV-2 infection that is reasonably assumed to have been transmitted vertically in utero. After preterm delivery to a SARS-CoV-2 positive mother, testing for SARS-CoV-2 infection in neonates is crucial. Both neutropenia and lymphopenia should alert physicians to test for SARS-CoV-2 infection and also to follow the case.